Role of complementary and alternative medicine in treatment and prevention of obesity; Molecular strategies to recommended acceptance - Atif Amin, Baig; Nordin, Simbak; Yasrul Izad, Abu Bakar (2019)
The incidence of obesity is increasing at an alarming rate which has led to a surge the obesity-related morbidity in the world. It is now a most evident problem in world’s population therefore, it needs to be addressed [1]. According to WHO, obesity is defined as BMI equals to or greater than 30kg/m2 which is the accumulation of fat in adipose tissue to such an extent that may be fatal [2]. Obesity is now replacing malnutrition, infectious and contagious diseases as the most vital contributor to ill health. The obesity-related health problem poses a burden on the health care system and lowers the quality of life of obese people. Particularly, it causes many chronic conditions like hypertension, cardiovascular diseases, diabetes type, kidney stones, respiratory issues, gout, arthritis, stroke, chronic fatigue sleep disorders and certain types of cancer such as breast and prostate cancer [2,3]. The epidemic of obesity is due to a sedentary lifestyle, minimal or no physical activity, intake of saturated fatty acid, high calories carbohydrates, carbonated drinks, and preserved food and sometimes genetic involvement is susceptible [4]. Without modifying lifestyles through culture and environment, it would be difficult to attain healthy life patterns. Improved patient health, quality of life and reduced cost of care of patients with obesity and other obesity-related health issues will not be recovered and resolved by clinical interventions alone [5-7].